The Relationship Between Physical Activity and Life Satisfaction: The Mediating Role of Social-Physique Anxiety and Self-Esteem - Gülhazal Özgökçe; Sinan Yıldırım (Pamukkale University, 2023)
The primary aim of the study was to investigate the relationship between physical activity, life satisfaction, and the mediating effects of social-physique anxiety and self-esteem. Furthermore, this study assessed the measurement invariance of research models according to gender and age. A total of 334 participants (29.43 ± 8.17 years) completed the measures. Path analysis was utilized to appraise the research models. The research models exhibited excellent fit based on the data fit index values. The findings of the study showed a positive relationship between physical activity and both self-esteem and life satisfaction. In contrast, a negative relationship was observed between social-physique anxiety and physical activity. Social-physique anxiety was negatively related to self-esteem and life satisfaction. Furthermore, social-physique anxiety played a mediating role in the correlation between physical activity and life satisfaction. Additionally, self-esteem was a mediator in the relationship between social-physique anxiety and life satisfaction. Physical activity directly and indirectly positively impacted life satisfaction, mediated by social-physique anxiety and self-esteem. Eventually, the finding highlights physical activity's significance in mitigating social-physique anxiety and promoting self-esteem and life satisfaction. Hence, promoting physical activity can yield positive outcomes for both physical and psychological well-being, contributing to an overall improvement in quality of life. Encouraging regular physical activity can be incorporated into public health campaigns and wellness programs, as well as in individualized health plans.